Volume 8: 31st Mechanisms and Robotics Conference, Parts a and B 2007
DOI: 10.1115/detc2007-34601
|View full text |Cite
|
Sign up to set email alerts
|

Contact Stress Reduction Mechanisms for the CAM-Based Infinitely Variable Transmission

Abstract: The Cam-based Infinitely Variable Transmission (IVT) is a new type of ratcheting IVT based on a three dimensional cam and follower system which provides unique characteristics such as generating specific functional speed ratio outputs including dwells, for a constant velocity input. This paper presents several mechanisms and design approaches used to improve the torque and speed capacity of this unique transmission. A compact, lightweight, and capable differential mechanism based on a cord and pulley system is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…To calculate the tangential and normal vectors at the first point, the last row of the calculated theoretical cam vector is removed, and the penultimate row is moved to the first row to form a new vector. Due to the large number of points and the dense distribution of points, according to Lagrange's mean value theorem, the slope of the tangential vector at this point is equal to the vector direction of the line between the two adjacent points, as shown in Formula (15).…”
Section: Cam Envelopementioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the tangential and normal vectors at the first point, the last row of the calculated theoretical cam vector is removed, and the penultimate row is moved to the first row to form a new vector. Due to the large number of points and the dense distribution of points, according to Lagrange's mean value theorem, the slope of the tangential vector at this point is equal to the vector direction of the line between the two adjacent points, as shown in Formula (15).…”
Section: Cam Envelopementioning
confidence: 99%
“…Hua [14] found that the smooth surface of the cam can be reduced by 53% maximum equivalent Von Mises stress. In the experiment, by considering using the constant speed in the staying itinerary, the contact stress was reduced to 41% [15]. Hus [16] adopted a cam with double-concave surface translation from the moving part to reduce the contact stress of the cam's equal pathway.…”
Section: Introductionmentioning
confidence: 99%
“…6 [32 , 33]. This small region exhibits a very high contact stress during the active region of the cam, when the most significant loading of the followers occurs [6]. As mentioned in earlier section, both the cam and the follower were made of mild carbon steel and the plastic deformation starts when the contact pressure reaches (2.8) of the yield stress.…”
Section: Contact Load Formulationmentioning
confidence: 99%
“…Hua et al, found that the smooth surface of cam profile provides a 53% reduction in maximum subsurface Von Mises stress [5]. Contact stress can be reduced to 41% experimentally taking into consideration the dwell stroke for a constant velocity of the cam [6]. SolidWorks, Cosmosmotion and Algor softwares were used by Ghazalli to determine the stress concentration at the point of contact using the finite element analysis [7].…”
Section: Introductionmentioning
confidence: 99%